Operation regional harmony: a study of defense communities implementing joint land use studies - Clanahan, Christopher Michael (Kansas State University, 2021)
Propelled in the United States during the 20th century, land use compatibility issues between military installations and neighboring communities amplified due to rapid population growth, sprawling regional development, and limited intergovernmental planning. The evolution, expansion, and densification of defense communities have resulted in many multilateral consequences often exacerbated or alleviated by institutional willingness to participate in cooperative regional planning. One federal response to these physical incompatibilities in defense communities is the Joint Land Use Study (JLUS) program. The JLUS program is an ideal candidate for study since it is implemented nationally, universally, and is multilaterally motivated. As deliberations concerning another Base Realignment and Closure (BRAC) round remain open, scholarship on defense communities and policy responses to physical incompatibilities remains critical for supporting the long-term compatibility between civilian development and military readiness. This cross-sectional study performs the first ex-post evaluation of the program by surveying military and civilian stakeholders from all 55 sites which conducted a JLUS between 2013 and 2017. The study also performs a pilot study on the policy Delphi to gauge its validity and suitability as a methodological instrument in planning policy research. Finally, interviews conducted with civilian planners with JLUS experience are used to assess the practicality of conducting joint studies in other contexts. The inferences from this study will aid planners, both military and civilian, to reflect on and compare their own regional planning efforts and outcomes to others potentially fostering the diffusion and adoption of more successful planning practices.
Keywords: Land use planning; Defense communities; Military planning; Regional planning; Policy delphi; Evaluation